Aplikasi Smart Health For Mini Hospital Al-Fath Berbasis Android - Khairil Anam; Moch Hatta; M. Farkhan (Puslitbang Sinergis Asa Professional, 2022)
In today's digital era, hospitals need to continue to innovate so that health services are more accessible and accessible to patients wherever they are. Conditions like this also require hospital human resources to understand information technology, especially when they have to register online or when patients teleconsult via mobile. The phenomenon of digitalization in the medical world makes hospitals must be ready to turn into smart hospitals so that the flow of registration and consultation treatment for patients is more flexible. In the world of hospital business, in this digital era, hospitals or polyclinics are also required to immediately adjust to the development of the times so that they can continue to exist in providing health services to the community who continue to demand high satisfaction in the services provided by hospitals or polyclinics. One of the polycinics located in the border area of Surabaya Sidoarjo is the Al-Fath mini hospital polyclinic. As one of the business units that provide health services to the community, Al-Fath Polyclinic needs to implement a strategy of using Smart Health in the business imposed, because people nowadays use a lot of digital smartphone access for activities and seek information specifically on what is needed in the world of health. Therefore, the implementation of the Smart Health digital strategy is needed for the digital development of Mini Hospital Al-Fath.